2005
DOI: 10.1258/1357633054461976
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider perspectives on home telecare: Preliminary results from a randomized controlled trial

Abstract: A randomized controlled trial of home telecare for the management of acute exacerbations of chronic obstructive pulmonary disease has been undertaken in the north-west of England. A videophone was used that communicates via the ordinary telephone network. The intervention period for each participant was two weeks. Participants in the telecare arm of the trial were asked to complete logbooks to record their experiences of each telecare encounter. A simple, self-completed, 10-item questionnaire was used that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 7 publications
(10 reference statements)
2
43
1
Order By: Relevance
“…Differences in perceptions between patients and providers, whereby patients show a higher readiness to use telecare, were found in previous research [25]. Providers show more scepticism about the “faceless counselling” and assume lower patient compliance with tele-nurse advice [26, 27].…”
Section: Discussionmentioning
confidence: 89%
“…Differences in perceptions between patients and providers, whereby patients show a higher readiness to use telecare, were found in previous research [25]. Providers show more scepticism about the “faceless counselling” and assume lower patient compliance with tele-nurse advice [26, 27].…”
Section: Discussionmentioning
confidence: 89%
“…In general, patients consistently report more positive views of telehealth, including home telecare, than do service providers [22]. Although most studies that examine patient satisfaction with telehealth, including telerehabilitation, report high satisfaction rates, the main area of dissatisfaction reported is generally with technical difficulties [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite recognizing the importance of the patient’s perspective, it remains absent from many studies [20], as was similarly reported by Mair et al in 2000 [21]. In telehealth, the patient’s perspective is generally documented through the concept of satisfaction and is reported using questionnaires and surveys, primarily addressing the technical aspects of using the technology and the communication between the participants [22]. …”
Section: Introductionmentioning
confidence: 99%
“…However, there was no difference in perceptions of accessibility. Although there were significant differences between the perceptions of the users group and the non-users group, all respondents had a positive perception of service benefits [13,20,21,33,34]. In other words, people had positive expectations for mobile health monitoring services.…”
Section: Discussionmentioning
confidence: 99%